2014
DOI: 10.1371/journal.pgen.1004418
|View full text |Cite
|
Sign up to set email alerts
|

Digital Genotyping of Macrosatellites and Multicopy Genes Reveals Novel Biological Functions Associated with Copy Number Variation of Large Tandem Repeats

Abstract: Tandem repeats are common in eukaryotic genomes, but due to difficulties in assaying them remain poorly studied. Here, we demonstrate the utility of Nanostring technology as a targeted approach to perform accurate measurement of tandem repeats even at extremely high copy number, and apply this technology to genotype 165 HapMap samples from three different populations and five species of non-human primates. We observed extreme variability in copy number of tandemly repeated genes, with many loci showing 5–10 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 80 publications
(88 reference statements)
1
74
0
Order By: Relevance
“…Due to their high mutability, tandem repeats can mutate away 57 from linkage with surrounding SNPs, and therefore SNP association studies are not 58 expected to pick up all of the heritability caused by hypermutable variants. Studies 59 using large numbers of tandem repeat loci have shown that tandem repeat variants are 60 usually very weakly linked with surrounding SNPs [4][5][6]. These studies highlight how 61 SNP data can be uninformative about hypermutable loci, supporting the hypothesis 62 that hypermutable loci are sources of missing heritability.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Due to their high mutability, tandem repeats can mutate away 57 from linkage with surrounding SNPs, and therefore SNP association studies are not 58 expected to pick up all of the heritability caused by hypermutable variants. Studies 59 using large numbers of tandem repeat loci have shown that tandem repeat variants are 60 usually very weakly linked with surrounding SNPs [4][5][6]. These studies highlight how 61 SNP data can be uninformative about hypermutable loci, supporting the hypothesis 62 that hypermutable loci are sources of missing heritability.…”
mentioning
confidence: 94%
“…Recent advances in sequencing technology [42,43,45] and tandem repeat 387 genotyping [6,44,46,47] provide hope that some hypermutable elements will be included 388 in future studies of genetic heritability and genetic disease. Nevertheless, some of the often caused by expansion [14,18].…”
mentioning
confidence: 99%
“…Understanding the possible role of this variation in gastrointestinal impairment and viral infection would be aided by more extensive testing of copy number in affected cohorts and controls with accurate quantitative techniques such as digital copy number estimation 1,6 or massively parallel sequencing. 10 Phase and haploid copy number could also be established in multigenerational families including those…”
Section: Resultsmentioning
confidence: 99%
“…If not due to dosage, any possible effects of a deletion would require alternative mechanisms such as enhancer adoption by genes flanking the REXO1L1 cluster 7 or the release of other genes from epigenetic control. 6 …”
Section: Microdeletion or Euchromatic Deletion Variant?mentioning
confidence: 99%
“…Indeed, STR has become an essential marker for mapping quantitative trait loci (QTL) due to their high variability and easy amplification by PCR (Georges et al 1993;Lipkin et al 1998;Van Tassell et al 2000;Ashwell et al 2001;Schnabel et al 2005). Furthermore, the exploration of the relationship between STRs with nearby SNPs can further help explain the results from SNP-based genome wide association studies (Brahmachary et al 2014). Although previous studies have reported that most STRs can be tagged by SNPs (McClure et al 2012(McClure et al , 2013, these conclusions were mainly based on a rather limited number of known microsatellites.…”
Section: Introductionmentioning
confidence: 99%